The addition of omeprazole to ondansetron for treating chemotherapy-induced nausea and vomiting in pediatric cancer patients - Perjuangan Dapot Hamonangan Simbolon; Selvi Nafianti; Pertin Sianturi; Bidasari Lubis; Aznan Lelo (Indonesian Pediatric Society, 2018)
Background Chemotherapy-induced nausea and vomiting are some of the most disturbing side effects in pediatric cancer patients. The standard recommendation is the use of 5-hydroxytryptamine 3 receptor antagonist, such as ondansetron, to treat these symptoms. Despite this treatment, more than 50% of patients still experience nausea and vomiting. Objective To evaluate the effect of the addition of omeprazole to ondansetron in the treatment of chemotherapy-induced nausea and vomiting. Methods A double-blind, randomized, controlled trial was conducted at Haji Adam Malik Hospital, Medan, North Sumatera, from March to May 2016. Subjects were children aged 1 to 18 years, diagnosed with cancer, and who received intravenous chemotherapy. Patients were randomized to receive either a single dose of ondansetron (0.5 mg/kg) plus placebo or ondansetron (0.5 mg/kg) plus omeprazole (0.5 mg/kg). The severity of nausea and vomiting were measured using the Rhodes index of nausea, vomiting, and retching during the 24 hours after initiation of emetogenic chemotherapy. The primary outcome of efficacy was the proportion of patients who achieved complete response (lack of nausea/vomiting). Statistical analysis was performed by Chi-square and Fischer’s exact tests. Results Seventy eligible pediatric patients were randomized into two groups: 32 subjects in the ondansetron + placebo group and 38 others in the ondansetron + omeprazole group. The therapy failed in 50% (16/32) of the ondansetron + placebo group and 18.4% (7/38) of the ondansetron + omeprazole group. There was a significant difference in the clinical response between groups (P=0.01). Conclusion The addition of omeprazole to ondansetron for the treatment of chemotherapy-induced nausea and vomiting is more effective than administration of ondansetron alone.